GALERI SASIRANGAN DI BANJARMASIN - Budiman, IGusti Bagus Arif; Agusniansyah, Nursyarif (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
The purpose of the Sasirangan Gallery design in Banjarmasin is to serve as an educational medium for local culture and a reminder for the local community, especially future generations, so that the Sasirangan fabric tradition is preserved. Sasirangan fabric, which has various motifs and is derived from South Kalimantan's signature knitting process, has become an important part of the industry in Banjarmasin. However, interest in this fabric varies with the times and trends, so preservation and promotion efforts are needed. The architectural problem that arises is how to design a Sasirangan Gallery that can be a modern promotional platform. The proposed solution is the use of the